Kedudukan Hukum Pekerja Freelance dalam Kondisi Perusahaan Pailit - Nur Faizatus Sholehah; Dipo Wahjoeono (Media Hukum Indonesia (MHI), 2026)
This study examines the legal status of freelance workers as concurrent creditors in bankruptcy proceedings. Freelance workers, as service providers who do not have an employment relationship with a company, are entitled to receive payment for the services they provide. However, in bankruptcy proceedings, freelance workers face limitations on their rights as concurrent creditors. This research analyzes the legal standing of freelance workers in bankruptcy proceedings and how their rights are protected. The results of the study indicate that freelance workers have a weak position as concurrent creditors and require better legal protection to ensure the fulfillment of their rights. The findings also show that freelance workers, as concurrent creditors, have limited rights in bankruptcy proceedings, such as lower payment priority compared to secured and preferred creditors. This study further finds that freelance workers need stronger legal protection to ensure their rights are fulfilled during bankruptcy proceedings. Therefore, this research is expected to contribute to the development of bankruptcy law in Indonesia, particularly with regard to the protection of freelance workers’ rights.